Low‐dose preoperative radiation, resection, and reduced‐field postoperative radiation for soft tissue sarcomas. Issue 3 (18th April 2021) - Konieczkowski, David J.; Goldberg, Saveli I.; Raskin, Kevin A.; Lozano‐Calderon, Santiago; Mullen, John T.; Chen, Yen‐Lin; DeLaney, Thomas F.
Abstract: Background and Objectives: Radiotherapy (RT) enables conservative surgery for soft tissue sarcoma (STS). RT can be delivered either pre‐operatively (PreRT) or postoperatively (PORT), yet in some patients, neither approach is fully satisfactory (e.g., urgent surgery or wound healing risk prevents PreRT, yet PORT alone cannot cover the entire surgical field). We hypothesized that, in such situations, low‐dose PreRT (LD‐PreRT) would decrease the risk of intraoperative tumor seeding and thus permit PORT to a reduced volume (covering the high‐risk tumor bed but not all surgically manipulated tissues). Methods: We identified a single‐institution retrospective cohort of 78 patients treated with LD‐PreRT (10–30 Gy), resection, and PORT between 1980 and 2018. Results: At a median follow‐up of 8.2 years, 8‐year overall survival (OS) was 65.9%, disease‐free survival (DFS) 50.5%, and local control (LC) 76.7%; in 45 patients with extremity/superficial trunk (E/ST) STS, 8‐year LC was 80.9%. Both before and after propensity score adjustment, there were no differences in OS, DFS, or LC between this cohort and a separate cohort of 394 STS (221 E/ST‐STS) patients treated with surgery and PORT alone. Conclusions: In patients for whom neither PreRT nor PORT alone is optimal, LD‐PreRT may prevent intraoperative tumor seeding and enable PORT to a reduced volume while preserving oncologic outcomes.